METHODOLOGICAL ASPECTS OF SURGICAL APPROACH IN VICTIMS WITH SEVERE MULTIPLE CRANIOFACIAL TRAUMA IN CONSIDERATION OF SEVERITY OF TRAUMATIC INJURY - Yu. A. Shcherbuk; D. Yu. Madai; S. V. Gavrilin; A. Yu. Shcherbuk; K. A. Absava; O. D. Madai (Вестник хирургии имени И.И. Грекова)
It is important to improve the medical care system and treatment of victims, introduce new methods of treatment and attract the multidisciplinary specialists in the cases of multitrauma. An integrated approach is required for the identification of different character and severity of multiple craniofacial injuries and the development of rational surgical strategy on this base. Different scales such as AIS, CRIS, ISS, PTS, TRISS, TRISSCAN, CRAMS et.al. were created abroad. Another approach to medical strategy was developed in the department of military surgery of Kirov Military Academy in the late nineties. It was based on investigating of possibilities of surgical strategy optimization by application of objective evaluation of the severity of injuries (military surgery - SP, SG, SS). Given treatment strategy of victims with multiple craniofacial trauma resulted in double reduction of quantity of suppurative and septic complications (from 10,5% to 4,1%). It gave the possibility to reduce the lethality from 6,4% to 4,0%. At the same time a hospital stay was shortened and the strategy allowed obtaining satisfactory functional results of treatment and avoiding reinterventions for removal of posttraumatic facial deformations.